TINGKAT KEASAMAN (pH) DAN OKSIGEN TERLARUT SEBAGAI INDIKATOR KUALITAS PERAIRAN SEKITAR MUARA SUNGAI CISADANE - Susana, Tjutju (Jurnal Teknologi Lingkungan Universitas Trisakti, 2009)
Acidity and dissolved oxygen as indicator of water quality for Cisadane estuary. A lot of waste which flows into the rivermouth of Cisadane River were considered to influence to degree of acidity (pH) value and oxygen concentration of that waters. The change of those values will be indicator of waters quality. Based on that condition, the research at the rivermouth of Cisadane and at vicinity was carried out in 2003 – 2005 and two different monsoon. As long as those periods the waters quality were increased, the degree of acidity was increased between 0.88% - 3.49%, whereas oxygen concentration between 12.55% - 39.15%. The influence of river flows with a lot of organic matter were caused the lower of oxygen concentration and pH value. The oxygen concentration at the Cisadane River just 1.89 ml/l and pH 6.8. The lowest of those parameters were equal to the highest of nitrate concentration (29.53 μgA/l). Nevertheless those condition were better after to river outside.